Niosome-Based Hydrogel of Quince Extract: A Promising Strategy for Expedited Full-thickness Wound Healing in Rat - Ebrahimnejad, Pedram; Heydarabadi, Paria Fadaee; Amiri, Fereshteh Talebpour; Mirzaee, Fatemeh; Ahmadi, Melika; Shahani, Somayeh (Current Drug Delivery, 2025)
BackgroundThe regeneration of tissue damage involves a series of molecular and cellular events that can be mediated by various natural compounds. Recent studies have highlighted the anti-inflammatory, anti-ulcer, and skin-protecting properties of Cydonia oblonga (Quince), which are mainly attributed to phenolic compounds. These compounds may have some drawbacks when targeting wound applications, including low bioavailability at the wound site. Moreover, to overcome these limitations, surfactant-based nanovesicular systems have been developed as carriers of such compounds for wound healing.ObjectiveThis study aimed to highlight the possible therapeutic potential of niosome-based hydrogel from Quince extract to stabilize and deliver the related bioactive compounds to full-thickness wounds in rats.MethodsThe niosomal hydrogel was prepared using a thin-film hydration method with the fruit extract (70% methanol). The formulation was optimized by evaluating size, zeta potential, dispersion index, and drug encapsulation efficiency. Full-thickness wounds were created on the dorsal cervical area of Wistar rats, and histopathological analysis of biopsy specimens was conducted on the 12th day of treatment.ResultsUnder the study conditions, niosomal hydrogel displayed good physicochemical stability. Histopathological findings demonstrated that niosomal gel promoted angiogenesis, fibroblast maturation, collagen deposition, keratinization, and epidermal layer formation more effectively than control and hydrogel base. Furthermore, niosomal gel treatment markedly reduced inflammation. The total phenol concentration was determined to be 13.34 ± 0.90 mg gallic acid equivalents per gram of dried extract.ConclusionThe niosomal hydrogel containing C. oblonga extract shows potential as a novel approach for wound healing, warranting further investigation in this field.
Keywords: rat